Clinical and echocardiographic outcomes with new‐onset left bundle branch block after SAPIEN‐3 transcatheter aortic valve replacement. Issue 1 (15th November 2022) - Sammour, Yasser M.; Lak, Hassan; Chahine, Johnny; Abushouk, Abdelrahman; Chawla, Sanchit; Kadri, Amer; Alkhalaileh, Feras; Kumar, Sachin; Ghimire, Bindesh; Svensson, Lars; Popovic, Zoran; Tarakji, Khaldoun; et al.
Abstract: Background: New‐onset left bundle branch block (LBBB) can develop after transcatheter aortic valve replacement (TAVR) resulting in worse outcomes. Aims: Describe clinical and echocardiographic outcomes with new‐onset LBBB after TAVR. Methods: We included consecutive patients who underwent transfemoral‐TAVR with SAPIEN‐3 (S3) valve between April 2015 and December 2018. Exclusion criteria included pre‐existing LBBB, right BBB, left anterior hemiblock, left posterior hemiblock, wide QRS ≥ 120ms, prior permanent pacemaker (PPM), and nontransfemoral access. Results: Among 612 patients, 11.4% developed new‐onset LBBB upon discharge. The length of stay was longer with new‐onset LBBB compared with no LBBB [3 (2–5) days versus 2 (1–3) days; p  < 0.001]. New‐onset LBBB was associated with higher rates of 30‐day PPM requirement (18.6% vs. 5.4%; p  < 0.001) and 1‐year heart failure hospitalizations (10.7% vs. 4.4%; p  = 0.033). There was no difference in 3‐year mortality between both groups (30.9% vs. 30.6%; p  = 0.829). Further, new‐onset LBBB was associated with lower left ventricular ejection fraction (LVEF) at both 30 days (55.9 ± 11.4% vs. 59.3 ± 9%; p  = 0.026) and 1 year (55 ± 12% vs. 60.1 ± 8.9%; p  = 0.002). These changes were still present when we stratified patients according to baseline LVEF (≥50% or <50%). New‐onset LBBBs were associated with a higher 1‐year LV end‐diastolic volume index (51.4 ± 18.6 vs. 46.4 ± 15.1 ml/m 2 ; p  = 0.036), and LV end‐systolic volume index (23.2 ± 14.1 vs. 18.9 ± 9.7 ml/m 2 ; p  = 0.009). Compared with resolved new‐onset LBBB, persistent new‐onset LBBB was associated with worse LVEF and higher PPM at 1 year. Conclusions: New‐onset LBBB after S3 TAVR was associated with higher PPM requirement, worse LVEF, higher LV volumes, and increased heart failure hospitalizations, with no difference in mortality.